L’EXCÈS – L’USINE (1982), DE LESLIE KAPLAN: uma tradução comentada (e inédita) para a língua portuguesa - CÂMARA, ANDREA MARLEY CHAGAS (2023)
The general objective of this monograph was to produce an annotated translation into Brazilian Portuguese of the contemporary French work L’excès - L’usine, written by Leslie Kaplan and originally published in 1982 (Hachette/P.O.L.). To this end, specific objectives were established: analyze the author’s and work’s status in the departure context; define a translation stance consistent with the author's style and interpretation of the work; identify and find well-founded solutions to difficulties in the translation process. A biobibliographical survey of the author was carried out together with readings of the book and collateral texts, followed by the translation and critical analysis stages. The translation result, O excesso – A fábrica, was presented together with the analytical and decision-making observations considered relevant. The work used the theoretical basis of translation scholars such as Lawrence Venuti (1995) and Michaël Oustinoff (2011), concerning translation methods, operations and perspectives, also using the systematization of literary criticism proposed by Antoine Berman (1995) and creative translation in poetry, according to Haroldo de Campos (2003). The peculiar style and symbolic richness of the text delimited a conciliatory translation attitude, focused either on literality or on meaning, according to textual needs. This unprecedented translation into Portuguese of a literary work endowed with stylistic and contextual richness, in addition to contributing to academic discussions on the subject, offers the possibility of increasing access to Leslie Kaplan's work for an audience potentially prevented from doing so by language barriers.